Cover Image. (13th February 2020) - Zhang, Yixue; Huang, Jiangchang; Fang, Xiaoming; Ling, Ziye; Zhang, Zhengguo
Abstract : The cover image is based on the Research Article Optimal roof structure with multilayer cooling function materials for building energy saving by Yixue Zhang et al., https://doi.org/10.1002/er.4969 .